Root Systems of some Desert Plants at Churu, Rajasthan - Sharma, B. M. (Indian Forester, 1968)
Root systems of six species, viz., Aerva javanica (Burm.f.) Spreng., Calligonum polygonoides Linn., Calotropis procera R. Br., Cenchrus biflorus Roxb., Prosopis spicigera Linn. and Tephrosia purpurea Pers. Were studied both on sandy plain and sand dunes. The study reveals that the plants usually develop long root systems which tap moisture from the deeper zones of the soil. Further the laterals spread freely since the vegetation is open and competition among the roots is minimum. All the plants possessed tap roots except Cenchrus biflorus Roxb. Which had the fibrous root system. The plants which had very little branching included Calotropis procera R. Br. On plains and Calligonum polygonoides Linn. On dunes and plains. The proportion of root to shoot is very large in all the cases except Cenchyus biflorus Roxb. A maximum water content was observed in the roots of Calotropis procera R. Br., Cenchrus biflorus Roxb. And Aera javanica (Bunn.f.) Spreng.